Combined Carburizing and Shot Peening to Increase Gear Sprocket Surface Hardness - Bambang Hari Priyambodo; Lilik Dwi Styana; Martinus Heru Palmiyanto; Kaleb Priyanto; Rauuf Nur Fattah (Jurnal Polimesin, 2024)
The sprocket is a crucial motorcycle component that transferengine rotational force to the wheels. However,  friction between the chain and gear during the operation leads to wear. This study aimed to enhancethe surface hardness of sprocket by combining  pack carburizing and shot peening. Pack carburizing was conducted by embedding the sprocket in coconut shell charcoal powder and heating it to 850°C for 60 minutes,followed by quenching in water at 30°C. Shot peening was then applied to the carburized specimen using steel ball particles for 20 minutes at a pressure of 8 bar. Hardness testing was performed according tothe ASTM 92-17 Vickers method, andmicrostructuralanalysis was conducted  using Scanning Electron Microscopy (SEM) on the best specimen results. The hardness values for untreated, carburized, and carburized + shot peened specimens were found to be 284, 302, and 424 VHN, respectively. In this study, transverse observation of the specimen showed a carburizing layer with a depth of about 8 µm. The phenomenon was related to the increase in hardness of the carburized specimen, while the effect of shot peening for 20 minutes was about 100 µm from the surface of the specimen. This caused the hardness of the combined carburizing and shot peening specimen with a pressure of 8 bar for 20 minutes to increase hardness by about 49% compared to the non-treatment specimen. This combination significantly improved the surface hardness, potentially increasing the sprocket’s wear resistance and operational lifespan.Transverse analysis revealed an approximately 8 µmdeeo carburized layer, with the shot peening effect penetrating about 100µm from the surface. This treatment combination increased the specimen’s, suggesting a significant improvement in surface hardness, wear resistance, and overall durability of the sprocket.